Exploring Systemic Lupus Erythematosus Pathogenesis through Animal Models: A Systematic Review of Humanized and Pristane-Induced Lupus Mice - Airlangga, Dimas Ikhsan; Rahmawati, Hanifa Rizky; Susianti, Hani; Handono, Kusworini (Journal of Biomedicine and Translational Research, 2023)
Studies involving experimental animals to explore the pathogenesis of systemic lupus erythematosus (SLE) which leads to the selection of optimal therapy have been widely conducted. The well-known model used to study SLE includes the pristane-induced mouse model and the more recently developed humanized mouse model that implants human immune cells into immunodeficient mice. The current state of the research has yet to provide a systematic review that analyzes both model and its contribution to our understanding of SLE pathogenesis. This systematic review-based study aims to provide a comprehensive overview of the development and application of pristane-induced and humanized mouse models. We obtained several relevant article sources include: (1) Search Strategy, on databases such as PubMed, MEDLINE, ScienceDirect, and Cochrane by adjusting the protocols listed in the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA); (2) Eligibility based on exclusion and inclusion criteria; and (3) Data Extraction. The findings show that 30 articles are relevant to the subject matter. Several strains of mice were used in the model of the 0.5 pristane injection method and the humanized mice model. All studies showed similar patterns in the onset and manifestation of SLE in mice models with slight variations. The purpose of using the pristane injection method and humanized mice model is adjusted to the output of each study. A variety of research preferences can be used as a reason for choosing pristane and humanized cells transplanted SLE methods in making lupus model mice.